Brain Activations to Dyspnea in Patients With COPD - Reijnders, Thomas; Troosters, Thierry; Janssens, Wim; Gosselink, Rik; Langer, Daniel; Davenport, Paul W.; von Leupoldt, Andreas (Frontiers in Physiology, 2020)
We compared the perception and neural processing of respiratory sensations between 20 COPD patients and 20 healthy controls by means of respiratory-related evoked potentials (RREP) in the electroencephalogram (EEG). RREPs were induced by short inspiratory occlusions while 129-channel EEG was measured. COPD patients rated the occlusions as more intense and unpleasant (p’s<.001) and showed higher mean amplitudes for the RREP components P1 (p=.0004), N1 (p=.024), P2 (p=.019) and P3 (p=.018). Our results indicate that COPD patients demonstrate greater perception and neural processing of respiratory sensations, which presumably reflects the highly aversive and attention-demanding character of these sensations for COPD patients.